2016
DOI: 10.1088/0957-4484/28/1/015701
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electromechanical coupling on optical properties of InGaN quantum-dot based light-emitting diodes

Abstract: The impact of electromechanical coupling on optical properties of light-emitting diodes (LEDs) with InGaN/GaN quantum-dot (QD) active regions is studied by numerical simulations. The structure, i.e. the shape and the average In content of the QDs, has been directly derived from experimental data on out-of-plane strain distribution obtained from the geometric-phase analysis of a high-resolution transmission electron microscopy image of an LED structure grown by metalorganic vapor-phase epitaxy. Using continuum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…As a result, in the coupled region III free electrons in n-type WS 2 readily transfer to InGaN QDs leading to a quenching T emission in PL spectra. The band bending of InGaN QDs in the band diagram is caused by the spontaneous and piezoelectric polarization-induced electric field (31)(32)(33).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, in the coupled region III free electrons in n-type WS 2 readily transfer to InGaN QDs leading to a quenching T emission in PL spectra. The band bending of InGaN QDs in the band diagram is caused by the spontaneous and piezoelectric polarization-induced electric field (31)(32)(33).…”
Section: Resultsmentioning
confidence: 99%
“…It can be proved by the experimental results that white LEDs based on dodecagonal ring structures are a platform enabling a high-efficiency warm white light-emitting source. Recently, high-performance InGaN/GaN and InGaN/AlGaN nanowire heterostructure LEDs were prepared by different research groups [88][89][90][91][92][93][94]. A schematic diagram of a nanowire LED with an InGaN/AlGaN core-shell heterostructure is shown in Figure 5.…”
Section: Core/shell Structure Methodsmentioning
confidence: 99%
“…Over the past few years, various metal foils (e.g., Ti, Ta) [27,91] and metal-coated substrates (e.g., Al, Pt, Ti, Mo) [28,29,[92][93][94][95][96][97] have been investigated for the growth of AlGaN nanowire UV LED structures, motivated by the excellent physical properties of metals, including thermal and electrical conductivity, light reflection, as well as flexibility. In addition, by coating a metal layer to Si substrate one can also reduce the formation of SiN x .…”
Section: Metal Foils and Metal-coated Substratesmentioning
confidence: 99%
“…Additionally, an electrical resistance of 1.4 mΩ•cm was measured with a doping concentration of 5 × 10 19 cm −3 . Recently, Zhou et al demonstrated the controllable conductivity of FZ grown β-Ga 2 O 3 employing Nb as dopants [93]. By increasing the Nb doping concentrations, the electrical resistance of β-Ga 2 O 3 could be changed from 3.6 × 10 2 Ω•cm to 5.5 ×10 −3 Ω•cm, corresponding to a carrier concentration from 9.55 × 10 16 cm −3 to 1.8 × 10 19 cm −3 .…”
Section: Conductivity Control and Dopingmentioning
confidence: 99%